PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN MANGROVE DI DESA SEGARAJAYA, KECAMATAN TARUMAJAYA KABUPATEN BEKASI - Shahibah Yuliani; Nova Scorviana Herminasari (Jurnal Green Growth dan Manajemen Lingkungan, 2017)
The purpose of this research is to know the community participation management of mangrove forests in PAL Jaya Beach, Segarajaya Village Tarumajaya District, Bekasi. This study uses descriptive method, which aims to find information from by using the questionnaire (closed questionnaire), direct observation, interviews, and documentation. The subjects of this study were 25 people consisting of members of the Supervisory Society Group (POKMASWAS), Ikatan Pemuda Putera Daerah (IKAPUD), and other communitie. The results showed that community participation management of mangrove forests is relatively high from the aspects of planning and activities implementation (restoration). Community participation is also supported by several institutions cooperate such as socialization, mangrove planting, and development of mangrove forest area. However, community involvement in treating mangroves have been low. Related to community participation in utilizing mangrove forests is still educatiobal tourist area